Из материалов для комментария к «Капитанской дочке»: 12–25 [Notes and Queries on _The Captain’s Daughter_ (12—25)] - Ospovat, Alexander (Slavica Revalensia, 2022)
In these notes (see also the previous volume of Slavica Revalensia), Prof. Alexander Ospovat of UCLA identifies the sources of several segments of Alexander Pushkin’s novel _The Captain’s Daughter_, uncovers themes and events silently implied in the text (e. g., the protagonist’s sexual amusements, the money system in 18th-century Russia, a bath ritual in the Russian countryside, etc.), and reconstructs hidden meanings of individual episodes.